Implementasi Teknologi Metaverse Dengan Metode Kualitatif Pada Man Insan Cendekia Oki - Cipto Kurniawan; Tata Sutabri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This research aims to explore the application of metaverse technology at MAN Insan Cendekia OKI through a qualitative approach. In an educational context, the metaverse offers an immersive and interactive learning space, allowing students to interact in a virtual environment. Through in-depth interviews and observations, this research identifies the challenges and opportunities faced in the integration of this technology. The findings show that despite barriers in infrastructure and technological understanding, implementing metaverses can increase student engagement and create more engaging learning experiences. Recommendations are provided to improve technical support and training for educators in implementing the metaverse effectively.